PEMBUATAN GAME SHOOT ‘EM UP “ELEMENTAL RAIDERS” DENGAN FITUR ELEMEN DAN MULTIPLAYER MENGGUNAKAN UNITY - Brian Novern Tjandra; Jeanny Pragantha; Rendi Kristyadi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
“Elemental Raiders” is created using Unity. “Elemental Raiders” is a shooting game which features four basic elements of water, fire, air, and earth. Objects included in the game are enemies, power-ups, and environment. Testing is done with questionnaires filled out by 40 respondents. Results had shown that respondents enjoyed the element featured in this game and gained new experience.